Strike up the fun: Faculty bowling challenge 2023 / Mohd Alimukhti Mansor and Nik Aisyah Najwa Nik Mustaffa Shapri - Mansor, Mohd Alimukhti; Nik Mustaffa Shapri, Nik Aisyah Najwa (Faculty of Pharmacy, 2023)
In an effort to foster camaraderie and a competitive spirit among the members of the Faculty of Pharmacy, the Welfare and Recreation Club organized the "Santai Boling FF 2023" program on September 29, 2023. The event took place from 2:00 PM to 5:00 PM at Alam Lanes, Aeon Mall Shah Alam, Selangor, and was open to all Faculty of Pharmacy members, including staff, students, alumni, and their families. A total of 52 participants formed 13 groups and arrived promptly at 2:00 PM for registration and shoe collection. The program began with an opening address by Mr. Mohd Alimukhti Mansor, Chairman of the Welfare and Recreation Club of the Faculty of Pharmacy, followed by a 5-minute trial throw. The bowling competition commenced at 2:30 PM, allowing each team to participate in two rounds.